(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In this article, the level of performance speed and dynamics of athletes with different levels of adaptation to specific muscle activity is determined. The results of the study show that as the level of education increases, the coefficient of variation, which reflects the level of preparation of student-athletes in the group, decreases, that is, the levels of preparation of athletes approach each other. another. In particular, the coefficients of change among the handball players of the first stage students ranged from V=12.96% to V=15.98%, while for the students of the second stage, this indicator was V=12, 29%, reaching values ​​​​in the range of V=. 15.22%, but in stage III, it can be observed that they decreased (i.e. improved) to the values ​​of V = 11.58% and V = 14.37%.